Caring for Caregivers of High-Needs Children - Allie Peckham, Karen Spalding, Jillian Watkins, Cindy Bruce-Barrett, Marta Grasic and A. Paul Williams (Healthcare Quarterly, 2014)
The Caregiver Framework for Children with Medical Complexity, led by the Hospital for Sick Children, is a ground-breaking initiative that validates and supports the vital role of unpaid, family caregivers. The project uses a supported self-management model that includes a modest amount of funding to address pressing needs, and relies on Key Workers who provide ongoing education, counselling and care management to assist caregivers in planning over the longer-term. This paper describes the findings from a multi-stage, mixed-methods evaluation to examine the design and outcomes of the Caregiver Framework.
Keywords: family caregiving, patient centred care, care for the elderly, caregiver stress